(untitled) (Research, Society and Development, 2020)
This study aimed to assess the antimicrobial activity of various honeys against strains of gram-negative and -positive bacteria, as well as to determine the physicochemical parameters of these honeys. Seven honeys from various species of stingless bees were evaluated. The physical-chemical parameters evaluated were pH, moisture, water activity, acidity, ash, electrical conductivity and color. Antimicrobial activity was determined using disc diffusion agar tests and minimum inhibitory concentrations. We found that there was a relationship between the physical-chemical parameters and the antimicrobial activity. The minimum inhibitory concentration of 25% honey was able to inhibit the growth of both gram-positive and -negative bacteria; the greatest efficacy was verified for the species of bees Melipona mondury, M. quadrifasciata, Scaptotrigona bipunctata and Tetragona clavipes. Regarding synergism, Escherichia coli maintained its sensitivity profile in relation to all studied honeys combined with antimicrobials. An important factor to consider is the concentration of honey capable of sensitizing the microorganism, as it has been shown to be dependent on the species of the stingless bee. Nevertheless, all honeys showed antimicrobial activity in various methods of analysis. These data suggest that honey is a promising alternative to sensitize resistant microorganisms, for the health of humans and animals alike.